2016
DOI: 10.1016/j.fertnstert.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Novel correlates between antimüllerian hormone and menstrual cycle characteristics in African-American women (23–35 years-old)

Abstract: Objective To characterize normative anti-Müllerian hormone (AMH) levels and ascertain which factors are associated with AMH in a large cohort of reproductive-aged women. Design Cross-sectional study. Setting Study of the Environment, Lifestyle and Fibroids (SELF), a longitudinal study performed by the National Institute of Environmental Health Sciences in conjunction with a major health care provider in Detroit, Michigan. Patients 1,654 African-American women (AAW) aged 23-34 at recruitment. Interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
0
13
0
2
Order By: Relevance
“…Given the established relationship between age and AMH, as well as the confirmed association between age and AMH in our previous analysis of this cohort , age‐adjusted linear regression was performed to evaluate the association between obesity and its biomarkers and AMH. Age and quadratic age were both included in the model to allow for a nonlinear relationship between AMH and age.…”
Section: Methodsmentioning
confidence: 99%
“…Given the established relationship between age and AMH, as well as the confirmed association between age and AMH in our previous analysis of this cohort , age‐adjusted linear regression was performed to evaluate the association between obesity and its biomarkers and AMH. Age and quadratic age were both included in the model to allow for a nonlinear relationship between AMH and age.…”
Section: Methodsmentioning
confidence: 99%
“…AMH levels were log-transformed to account for non-normal distribution and all models were adjusted for age, BMI, and current hormonal contraception (HC), variables that were previously shown to be significantly associated with AMH levels in this cohort. 29 Recognizing the non-linear association between age and ovarian reserve, main effects models included both an age and an age quadratic term. Considering the natural, age-related decline in AMH levels occurring at 25 years, 3031 sensitivity analyses were performed to examine interactions between age and exposure variables.…”
Section: Methodsmentioning
confidence: 99%
“…39 In our study population, AMH levels began declining at 25 years of age, in keeping with previous studies, such that that binge drinking in the late twenties might accelerate the natural decline of AMH. 2931, 40 Considering that binge drinking is common in young women in the U.S., 7 this finding is important to examine further.…”
Section: Commentmentioning
confidence: 99%
“…Other studies have evaluated African-American women alone and observed a significant inverse effect. 21,22 Among African Americans, AMH was negatively correlated with current BMI 22 as well as current BMI, BMI at age 18, and highest lifetime BMI. 21 Though, the effect of BMI on ovarian reserve is debated, it is worth noting that race and ethnicity may have implications for the observed effects as well.…”
Section: Factors That Affect Ovarian Reserve and Its Markersmentioning
confidence: 99%
“…21 There have been several studies published that report no effect of obesity on AMH, as well as several that report a negative effect of obesity on AMH. 13,19,21,22 Though AFC is generally stable across menstrual cycles, it has been demonstrated to have some variability at high levels. 11 Possibly related to this, intercycle variability in AFC appears to be higher in overweight and obese women, which can limit the predictive utility in this population.…”
Section: Factors That Affect Ovarian Reserve and Its Markersmentioning
confidence: 99%